2002
DOI: 10.1523/jneurosci.22-09-03426.2002
|View full text |Cite
|
Sign up to set email alerts
|

Ca2+-Independent Feedback Inhibition of Acetylcholine Release in Frog Neuromuscular Junction

Abstract: The effect of membrane potential on feedback inhibition of acetylcholine (ACh) release was studied using the frog neuromuscular junction. It was found that membrane potential affects the functional affinity (K(i)) of the presynaptic M2 muscarinic receptor. The K(i) for muscarine shifts from approximately 0.23 microm (at resting potential) to approximately 8 microm (at a high depolarization). Measurements of Ca2+ currents in axon terminals showed that the depolarization-mediated shift in K(i) does not stem from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
32
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 45 publications
4
32
0
1
Order By: Relevance
“…This slow feedback inhibition, but not the fast one, is abolished at high depolarizations. The authors (51) suggested that the slow high affinity process, which is mediated by a second messenger, is probably important to maintain the rest (resting potential and resting concentration of ACh) level of release, whereas the low affinity fast process is likely to regulate the action potentialevoked ACh release.…”
Section: Discussionmentioning
confidence: 99%
“…This slow feedback inhibition, but not the fast one, is abolished at high depolarizations. The authors (51) suggested that the slow high affinity process, which is mediated by a second messenger, is probably important to maintain the rest (resting potential and resting concentration of ACh) level of release, whereas the low affinity fast process is likely to regulate the action potentialevoked ACh release.…”
Section: Discussionmentioning
confidence: 99%
“…After 2-3 h the pump was reactivated, and recording was resumed. Two to three hours of incubation was shown to be sufficient for PTX activation (51) and for reducing muscarine-mediated autoinhibition of ACh release (10). Here, it diminished Glu-induced inhibition (SI Fig.…”
Section: Methodsmentioning
confidence: 96%
“…Much of this suggested mechanism was supported experimentally (3)(4)(5)(6)(7)(8) by using mainly the cholinergic neuromuscular junction (NMJ), where the M 2 muscarinic autoreceptor (M 2 R) controls both slow feedback inhibition (9,10) and fast ACh release (6)(7)(8). However, the relevance of this hypothesis for other NTs was not investigated.…”
mentioning
confidence: 99%
“…2) In a number of preparations ACh release is enhanced by M 2 R antagonists (D'Agostino et al 1986;Morita et al 1982; Peteris and Ogren 1988;Slutsky et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, interaction was seen only when the M 2 R was occupied by a nonhydrolyzable muscarinic receptor agonist, muscarine. Addition of methoctramine, a specific M 2 /M 4 antagonist, abolished the interaction (Ilouz et al 1999).2) In a number of preparations ACh release is enhanced by M 2 R antagonists (D'Agostino et al 1986;Morita et al 1982; Peteris and Ogren 1988;Slutsky et al 1999).3) We have recently shown, in Xenopus oocytes, that M 2 R does indeed reside in a high-affinity state for ACh at resting potential (Ϫ60 mV) and in a low-affinity state at ϩ40 mV (Ben-Chaim et al 2003).A formal mathematical model of our hypothesis was provided by Yusim et al (1999). This model was further tested, and some of its key assumptions were supported by experimental results.…”
mentioning
confidence: 97%